Conjugal Visit: Juridical Review of the Fulfillment of Inmates' Rights in the Correctional Perspective - Niken Subekti Budi Utami; Octa Nadia Mellynda (Badan Strategi Kebijakan Hukum, 2022)
Imprisonment as a loss of independence should only limit the inmates' freedom of movement in a correctional institution. This interpretation rises a discourse that the fulfillment of other rights of inmates must be guaranteed, including the right to fulfill their sexual needs. A term that is known globally in order to fulfill this right is called a conjugal visit. This study seeks to describe the urgency and prospects of conjugal visit for inmates in Indonesia. In addition, this study aims to provide an overview of the arrangement and implementation of conjugal visit. This legal research was normative legal research supported by the results of interviews with resource persons. The data obtained from the literature research were analyzed descriptive-qualitatively with a legal systematic approach and legal comparison. The results of this study indicate that sexual needs are one of the human rights. They are the inmates' basic needs that must be fulfilled. The failure to fulfill these basic needs will have a negative impact both physically and psychologically. Based on the theory of basic human needs, the rules of international law, namely the Nelson Mandela Rules and the Bangkok Rules, as well as national law, namely the Republic of Indonesia Law Number 36 of 2009 concerning Health, conjugal visit can actually be implemented in Indonesia with clear legal bases in Indonesian law. Establishment of regulations regarding conjugal visit is done by comparing practices in other countries and aligned withn the Legal System Theory. These countries have similar backgrounds to Indonesia and have implemented conjugal visit, namely Pakistan, Turkey, and Saudi Arabia.